A core-shell structure material with wrinkled surface and its preparation method and application

Through the combination of the three-dimensional carbon fold shell layer and the foamed ball core, a green and environmentally friendly process is used to form a fold structure at high temperature, which solves the problems of complex preparation of surface fold core-shell structure materials in the prior art, small size and narrow absorption bandwidth in the existing technology. , achieves the effect of large size in millimeters, large specific surface area, and excellent electromagnetic wave absorption performance, and is suitable for complex electromagnetic environments and applications in multiple fields.

CN118440443BActive Publication Date: 2024-12-13NAT UNIV OF DEFENSE TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410763283.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2024-12-13
Estimated Expiration
2044-06-13

AI Technical Summary

Technical Problem

The existing surface pleated core-shell structure materials are complex and costly, and are usually at the micron level, with large density and narrow effective absorption bandwidth, which limits their application in complex electromagnetic environments.

Method used

The three-dimensional carbon fold shell is used to combine with the foamed sphere core, and the surface fold core of the foamed sphere is adsorbed through a carbon source and shrinks at high temperature to form a fold structure to achieve a surface fold core-shell structure material of a millimeter-level large size and high specific surface area. , without requiring additional adhesive, adopts a green and environmentally friendly and efficient preparation process.

Benefits of technology

It has realized a surface wrinkled core-shell structure material with large size in millimeters, large specific surface area and excellent electromagnetic wave absorption performance. It is environmentally friendly and efficient, which is convenient for industrial production, and has broadened its application in electromagnetic wave absorption, catalysis, adsorption, sensing and other fields. prospect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118440443B_ABST
    Figure CN118440443B_ABST
Patent Text Reader

Abstract

A core-shell structure material with a wrinkled surface, and a preparation method and application thereof, wherein the core-shell structure material with a wrinkled surface is formed by coating a foamed sphere core with a three-dimensional carbon wrinkled shell layer; the mass ratio of the three-dimensional carbon wrinkled shell layer to the foamed sphere core is 1:3-10. The preparation method comprises: (1) soaking the dried foamed sphere in a carbon source aqueous solution; (2) standing and drying, heating and shrinking to a stable state, and obtaining a core-shell structure material with a wrinkled surface. The core-shell structure material with a wrinkled surface, or a core-shell structure composite material with a densely packed surface wrinkles obtained by compounding in a frame with a periodic structure, is applied to the fields of electromagnetic wave absorption, catalysis, adsorption and sensing. In the core-shell structure material of the present invention, the three-dimensional carbon wrinkled shell layer is firmly combined with the foamed sphere core, has a large size of millimeters, a controllable morphology, diverse properties, a large specific surface area, and excellent electromagnetic wave absorption performance. The method of the present invention is environmentally friendly, green, efficient, convenient, low-cost, and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a core-shell structure material and a preparation method and application thereof, and in particular to a core-shell structure material with a wrinkled surface and a preparation method and application thereof. Background Art

[0002] Wrinkled structures are widely found in nature, such as the surface of white blood cells, paulownia bark, and the surface of human skin. Wrinkled structures provide a larger specific surface area, which can enhance the surface function, and the special wrinkled surface structure can significantly improve the microwave absorption performance of rare materials.

[0003] At present, the preparation methods of core-shell structure absorbing materials with surface wrinkles are mainly hydrothermal method, in-situ polymerization method, chemical deposition method, sol-gel method, etc. The main absorbing materials used are ferrite, carbon-based materials, magnetic metals and ceramic materials.

[0004] Qiao et al. prepared mushroom-shaped, honeycomb-shaped, and corolla-shaped Fe3O4@MnO2 microspheres by hydrothermal method, and achieved precise control of the thickness and morphology of the wrinkled shell by changing the reaction time and temperature (Chem Eng J, 2016, 304: 552). Zhang et al. successfully synthesized CoFe2O4@CNTs hollow microspheres with carbon nanotubes as wrinkled shells by chemical deposition (J Alloys Compd, 2017, 694: 309). An et al. prepared a soft ferromagnetic nanocore-shell structure Ketjen black / Fe3O4 by hydrothermal method, with an effective absorption bandwidth of 4.17 GHz at a matching thickness of 1.5 mm (Rare Met, 2022, 41: 3351-3359). However, the surface wrinkled core-shell structure obtained by the above method usually requires cumbersome or costly surface treatment of the core-shell structure.

[0005] In addition, surface wrinkled shell materials mainly include magnetic metal nanoparticles and carbon-based materials. The sizes of the core-shell absorbing materials prepared by them are mostly in the micron order, which is invisible to the naked eye. There are few reports of millimeter-sized surface wrinkled core-shell structure materials. In addition, there are also disadvantages of high density and narrow effective absorption bandwidth, which limits the application of surface wrinkled core-shell structure absorbing materials in increasingly complex electromagnetic environments. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a three-dimensional carbon wrinkled shell layer firmly combined with the foamed ball core, without the need to add additional adhesive, with a large size at the millimeter level, controllable morphology, and diverse properties. The foamed ball core has a large shrinkage ratio, a large specific surface area, and a surface wrinkled core-shell structure material with excellent electromagnetic wave absorption performance and its application.

[0007] The technical problem to be further solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a method for preparing a core-shell structure material with a surface wrinkle which is green and environmentally friendly, has an efficient and convenient preparation process, is low in cost, and is suitable for industrial production.

[0008] The technical solution adopted by the present invention to solve the technical problem is as follows: a core-shell structure material with a wrinkled surface, wherein the core-shell structure material with a wrinkled surface is formed by a three-dimensional carbon wrinkled shell layer covering a foamed ball core; the mass ratio of the three-dimensional carbon wrinkled shell layer to the foamed ball core is 1:3 to 10. The foamed ball as the core has a large shrinkage ratio, which can make the core-shell structure material with a wrinkled surface have a larger specific surface area.

[0009] Preferably, the average particle size of the core-shell structure material with wrinkled surface is 1 to 3 mm.

[0010] Preferably, the average thickness of the three-dimensional carbon wrinkle shell is 70-160 μm. If the shell is too large, it is easy to fall off, and if the shell is too small, it is difficult to form wrinkles.

[0011] Preferably, the specific surface area of ​​the core-shell structure material with a wrinkled surface is 6 to 40 mm -1 .

[0012] Preferably, the three-dimensional carbon wrinkled shell layer has a secondary wrinkle morphology.

[0013] Preferably, in the secondary wrinkle morphology, the wrinkle morphology of each level is furrow wrinkle, fold wrinkle, furrow / fold wrinkle, rough protrusion or irregular. The primary wrinkle exists on the secondary wrinkle.

[0014] Preferably, the carbon source of the three-dimensional carbon wrinkle shell layer is carbon nanotubes and / or graphene, etc. Different carbon materials form different wrinkle morphologies.

[0015] Preferably, the carbon nanotubes are multi-walled carbon nanotubes with an average length of 20 to 50 μm and an average diameter of 8 to 15 nm.

[0016] Preferably, the graphene sheet particle size is 4 to 8 μm.

[0017] Preferably, the foamed beads are one or more of polystyrene, polypropylene or polyurethane.

[0018] The technical solution adopted by the present invention to further solve the technical problem is as follows: a method for preparing a core-shell structure material with a wrinkled surface, comprising the following steps:

[0019] (1) Soaking the dried foaming beads in a carbon source aqueous solution so that the surface of the beads fully absorbs the carbon source, thereby obtaining foaming beads that absorb the carbon source;

[0020] (2) The carbon source absorbing foamed beads obtained in step (1) are allowed to stand and dry, and then heated to shrink to a stable state, thereby obtaining a core-shell structure material with a wrinkled surface.

[0021] The inventive idea of ​​the method of the present invention is: using foamed balls as wrinkling bases, carbon sources are adsorbed and dried on their surfaces to form a coating, and utilizing the characteristic of rapid shrinkage of the porous structure of the foamed balls when heated. As the volume of the balls shrinks, the core-shell structure undergoes mismatch deformation between the core and the shell of the foamed balls under the stimulation of external high temperature, generating in-plane compressive stress in the shell. Due to the stress mismatch between the carbon source shell and the core of the foamed balls, when the stress is higher than a critical value, the coating formed on the surface of the core will gradually shrink to form wrinkles.

[0022] Preferably, in step (1), the density of the foamed beads is 1 to 2 g / cm 3 .

[0023] Preferably, in step (1), the immersion temperature is room temperature and the time is 1 to 2 minutes. During the immersion process, a layer of carbon film is uniformly adsorbed on the surface of the foaming ball.

[0024] Preferably, in step (1), the particle size of the foamed beads is 4 to 5 mm. If the particle size is too small, it will be difficult to operate during the preparation process. If the particle size is too small, the surface area of ​​the corresponding ball core is too small, the shrinkage ratio of the foamed beads is too small, and the surface coating of the ball core is not easy to wrinkle.

[0025] Preferably, in step (1), the mass concentration of the carbon source aqueous solution is 0.2-3.0%. More preferably, the mass concentration of the carbon nanotube aqueous solution is 0.5-2.0%, and the mass concentration of the graphene aqueous solution is 1.0-2.5%. When the two are mixed, the mass ratio of multi-walled carbon nanotubes to graphene is 1:10-30. The method of the present invention can adjust the thickness of the wrinkled shell layer by changing the mass concentration of the carbon source aqueous solution. If the mass concentration is too low, the coating thickness is too thin and the wrinkled morphology formed is not obvious. If the mass concentration is too high, the coating thickness is too thick, resulting in unnecessary waste.

[0026] Preferably, in step (1), the carbon source aqueous solution is prepared by adding an aqueous slurry of the carbon source into water and performing ultrasonic dispersion, or directly performing ultrasonic dispersion on the aqueous slurry of the carbon source.

[0027] Preferably, the frequency of the ultrasonic dispersion is 40 to 80 kHz, the power is 60 to 100 W, and the time is 2 to 4 hours.

[0028] Preferably, in step (2), the temperature of the static drying is room temperature.

[0029] Preferably, in step (2), the temperature of the heating shrinkage is 110-150°C, and the time is 15-60 minutes (more preferably 20-45 minutes). The shrinkage speed can be regulated by controlling the heating temperature and time. If the temperature is too low, it will be difficult to form wrinkles, and if the temperature is too high, the foaming balls will melt.

[0030] The technical solution adopted by the present invention to further solve its technical problems is as follows: an application of a core-shell structure material with a wrinkled surface, and applying the core-shell structure material with a wrinkled surface, or a densely packed core-shell structure composite material with a wrinkled surface obtained by compounding it in a frame with a periodic structure, to the fields of electromagnetic wave absorption, catalysis, adsorption and sensing.

[0031] Preferably, the method for preparing the densely packed surface wrinkled core-shell structure composite material comprises the following steps:

[0032] (1) The core-shell structure material with wrinkled surface is densely arranged in a rectangular groove mold coated with adhesive to obtain a single-layer adhesive composite material; or the core-shell structure material with wrinkled surface is densely arranged in a rectangular groove mold, and then an elastomer is dotted in the gaps between the materials, and after standing and curing, a single-layer cured composite material is obtained;

[0033] (2) Multiple groups of single-layer adhesive composite materials are stacked in pairs in a frame structure with their uncoated surfaces connected to each other, or multiple groups of single-layer cured composite materials are stacked in a frame structure to obtain a core-shell structure composite material with densely packed surface wrinkles.

[0034] Preferably, in step (1), the inner length of the rectangular groove mold is ≥2 cm (more preferably 2-5 cm), the inner width is ≥2 cm (more preferably 2-5 cm), and the groove depth is 1-3 mm. More preferably, the core-shell structure material with surface wrinkles is densely arranged in an array in the rectangular groove mold, with the number being (12-15) columns*(12-15) rows.

[0035] Preferably, in step (1), the rectangular groove mold is made of one or more of polylactic acid, photosensitive resin or ABS plastic.

[0036] Preferably, in step (1), the adhesive includes one or more of double-sided tape, silicone glue or epoxy resin strong AB glue.

[0037] Preferably, in step (1), the elastomer includes one or more of silicone rubber, epoxy resin or polydimethylsiloxane, etc. More preferably, the elastomer is silicone rubber Ecoflex.

[0038] Preferably, in step (1), the temperature of the static curing is room temperature and the time is 2 to 4 hours.

[0039] Preferably, in step (2), the material of the frame structure is one or more of polylactic acid, photosensitive resin or ABS plastic.

[0040] Preferably, in step (2), the cavities in the framework structure for accommodating the core-shell structure composite material with densely packed surface wrinkles are arranged in an array. More preferably, the number of the cavity array arrangement is not less than 6 columns * 6 rows, and the outer dimension of the framework structure is not less than 18 cm * 18 cm.

[0041] Preferably, in step (2), the length and width of the two connected single-layer adhesive composite materials are equal or the length and width of the upper layer are 1 to 3 mm smaller than those of the lower layer. More preferably, the reduced length and width are equivalent to a core-shell structure material with a wrinkled surface, the purpose of which is to maximize the use of the material space as much as possible while changing the macroscopic pattern of the unit structure, in order to improve the electromagnetic wave absorption performance of the material.

[0042] Preferably, in step (2), the length and width of the multiple stacked single-layer cured composite materials are equal or the length and width of the upper layer are gradually reduced by 1 to 3 mm compared with the lower layer. More preferably, the reduced length and width are equivalent to a core-shell structure material with a wrinkled surface, the purpose is to maximize the use of the material space as much as possible while changing the macroscopic pattern of the unit structure, so as to improve the electromagnetic wave absorption performance of the material. More preferably, the number of the multiple stacked single-layer cured composite materials is 2 to 4.

[0043] Preferably, in step (2), when the stacked single-layer adhesive composite material or single-layer cured composite material is of equal size, the frame structure spacing between adjacent cavities is 2 to 6 mm, and the size of the frame structure cavity matches the size of the composite material. If the frame structure spacing is too large, electromagnetic waves are easily transmitted, and if the frame structure spacing is too small, it may cause unnecessary waste of materials.

[0044] Preferably, in step (2), when the sizes of the stacked single-layer adhesive composite materials or single-layer cured composite materials are unequal, the frame structure spacing between adjacent cavities on the lower side of the frame structure is 2 to 6 mm, the frame structure spacing between adjacent cavities on the upper side of the frame structure = the frame structure spacing between adjacent cavities on the lower side of the frame structure + (number of layers - 1) * gradually reduced size, and the inner cross-section of the frame structure cavity is stepped, matching the size of each layer of composite material. More preferably, multiple layers of single-layer adhesive composite materials or single-layer cured composite materials of unequal sizes are stacked in a center-aligned pyramid form.

[0045] Preferably, in step (2), the thickness of the frame structure = number of layers * thickness of a single layer of adhesive composite material or a single layer of cured composite material.

[0046] The rectangular groove mold and frame structure used in the present invention are both made by 3D printing.

[0047] The beneficial effects of the present invention are as follows:

[0048] (1) After the core-shell structure material particles with wrinkled surfaces of the present invention are cut, the shell layer does not fall off, indicating that the three-dimensional carbon wrinkled shell layer is firmly bonded to the foamed ball core, the wrinkled shell layer has stable properties, no additional adhesive is needed, the millimeter-level large size, different wrinkle morphologies and properties can be obtained by using carbon sources with different components, and the shrinkage ratio of the foamed ball core is large, so that the core-shell structure has a larger specific surface area and excellent electromagnetic wave absorption performance;

[0049] (2) The method of the present invention is green and environmentally friendly, does not use toxic and harmful reagents and expensive equipment, and the preparation process is efficient and convenient, low-cost, and suitable for industrial production;

[0050] (3) The surface wrinkled core-shell structure material of the present invention broadens the material basis of surface wrinkled core-shell structure and has potential application prospects in the fields of electromagnetic wave absorption, catalysis, adsorption, and sensing. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 This is a SEM image of Example 1 of the core-shell structure material with surface wrinkles of the present invention (wherein (a) is the secondary wrinkle morphology, (b) is the primary wrinkle morphology, and (c) is the cross-sectional morphology);

[0052] Figure 2 This is the SEM image of Example 2 of the core-shell structure material with surface wrinkles of the present invention (wherein (a) is the secondary wrinkle morphology, (b) is the primary wrinkle morphology, and (c) is the cross-sectional morphology);

[0053] Figure 3 This is the SEM image of Example 3 of the core-shell structure material with surface wrinkles of the present invention (wherein (a) is the secondary wrinkle morphology, (b) is the primary wrinkle morphology, and (c) is the cross-sectional morphology);

[0054] Figure 4 is a reflection loss diagram of application example 1 of the core-shell structure material with a wrinkled surface of the present invention;

[0055] Figure 5 is a reflection loss diagram of application example 2 of the core-shell structure material with a wrinkled surface of the present invention;

[0056] Figure 6 is a reflection loss diagram of application example 3 of the core-shell structure material with a wrinkled surface of the present invention;

[0057] Figure 7It is a top view and a cross-sectional view of the materials in the application examples 1 and 2 of the densely packed surface-corrugated core-shell structure composite material of the present invention densely packed in a rectangular groove mold (in the figure, 1 is the surface-corrugated core-shell structure material, and 2 is the polylactic acid rectangular groove mold);

[0058] Figure 8 3 is a schematic top view of the framework structure in application examples 1 and 2 of the composite material of the core-shell structure with densely packed surface wrinkles of the present invention (in the figure, 3 is the polylactic acid framework structure, and 3-1 is the cavity);

[0059] Fig. 9 It is a cross-sectional schematic diagram of the materials in the application example 2 of the composite material with a core-shell structure having close-packed surface wrinkles of the present invention stacked in a frame structure (in the figure, 1 is the core-shell structure material with a surface wrinkle, and 3 is the polylactic acid frame structure);

[0060] Fig.10 is a reflection loss diagram of application example 1 of the composite material with a core-shell structure having close-packed surface wrinkles of the present invention;

[0061] Fig.11 It is a reflection loss diagram of application example 2 of the core-shell structure composite material with densely packed surface wrinkles of the present invention. DETAILED DESCRIPTION

[0062] The present invention will be further described below in conjunction with the embodiments and drawings.

[0063] The polystyrene beads used in the examples and comparative examples of the present invention were purchased from Sanle Foam Filter Bead Environmental Protection Material Factory and had a density of 1.43 g / cm 3 ; The mass concentration of the aqueous slurry of multi-walled carbon nanotubes used is 2%, the average length of the multi-walled carbon nanotubes is 20-50 μm, and the average diameter is 8-15 nm, which is purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd.; The mass concentration of the aqueous slurry of graphene used is 5%, and the sheet particle size is 4-8 μm, which is purchased from Suzhou Tanfeng Graphene Technology Co., Ltd.; The polylactic acid rectangular groove mold and the polylactic acid frame structure used in the embodiments of the present invention and the comparative examples are both made by 3D printing; The raw materials or chemical reagents used in the embodiments of the present invention, unless otherwise specified, are all obtained through conventional commercial channels.

[0064] Reference Example 1 for Preparation of Multi-walled Carbon Nanotube Aqueous Solution

[0065] 100 g of aqueous slurry of multi-walled carbon nanotubes was subjected to ultrasonic dispersion at a frequency of 60 kHz and a power of 90 W for 3 h to obtain a multi-walled carbon nanotube aqueous solution with a mass concentration of 2%.

[0066] Reference Example 2 for Preparation of Graphene Aqueous Solution

[0067] 100 g of graphene aqueous slurry was added to 150 g of deionized water, and ultrasonic dispersion was performed for 3 h at a frequency of 60 kHz and a power of 90 W to obtain a graphene aqueous solution with a mass concentration of 2%.

[0068] Reference Example 3 Preparation Method of Mixed Aqueous Solution of Multi-walled Carbon Nanotubes and Graphene

[0069] After uniformly mixing 50 g of an aqueous slurry of multi-walled carbon nanotubes and 500 g of an aqueous slurry of graphene, the mixture was added into 450 g of deionized water, and ultrasonic dispersion was performed at a frequency of 60 kHz and a power of 90 W for 3 h to obtain a mixed aqueous solution of multi-walled carbon nanotubes and graphene (the mass concentration of the multi-walled carbon nanotubes was 0.1%, the mass concentration of the graphene was 2.5%, and the mass ratio of the multi-walled carbon nanotubes to the graphene was 1:25).

[0070] Example 1 of a core-shell structure material with wrinkled surface

[0071] The core-shell structure material with a wrinkled surface is formed by a three-dimensional multi-walled carbon nanotube wrinkled shell layer covering a polystyrene core; the mass ratio of the three-dimensional multi-walled carbon nanotube wrinkled shell layer to the polystyrene core is 1:10; the average particle size of the core-shell structure material with a wrinkled surface is 2 mm; the average thickness of the three-dimensional multi-walled carbon nanotube wrinkled shell layer is 79.69 μm; the specific surface area of ​​the core-shell structure material with a wrinkled surface is 10.32 mm -1 The three-dimensional multi-walled carbon nanotube wrinkled shell has a secondary wrinkle morphology, wherein the primary wrinkles are irregular and the secondary wrinkles are folded wrinkles.

[0072] Preparation method of a core-shell structure material with wrinkled surface Example 1

[0073] (1) Soaking dried polystyrene beads (4 mm in diameter) in the multi-walled carbon nanotube aqueous solution (mass concentration 2%) obtained in Reference Example 1 at room temperature for 1 min to allow the surface of the dried polystyrene beads to fully absorb the carbon source, thereby obtaining polystyrene beads absorbing the carbon source;

[0074] (2) The carbon source absorbing polystyrene beads obtained in step (1) are allowed to stand and dry at room temperature, and then placed in an oven and heated and shrunk at 130° C. for 30 minutes until they reach a stable state, thereby obtaining a core-shell structure material with a wrinkled surface.

[0075] By calculating the mass difference before and after the corrugated shell covers the polystyrene core, it is calculated that in the embodiment of the present invention, the mass ratio of the three-dimensional multi-walled carbon nanotube corrugated shell to the polystyrene core is 1:10.

[0076] like Figure 1As shown in (a) and (b), the core-shell structure material with surface wrinkles in the embodiment of the present invention is composed of a three-dimensional multi-walled carbon nanotube wrinkled shell layer covering a polystyrene core, and the average particle size is 2 mm; the three-dimensional multi-walled carbon nanotube wrinkled shell layer has a secondary wrinkle morphology, wherein the primary wrinkles are irregular and the secondary wrinkles are folded wrinkles.

[0077] like Figure 1 As shown in (c), the cross-section of the core-shell structure material particles with wrinkled surfaces of the embodiment of the present invention was observed by scanning electron microscopy. The average thickness of the three-dimensional multi-walled carbon nanotube wrinkled shell layer was 79.69 μm, and there was no shedding of the shell layer, indicating that the three-dimensional carbon wrinkled shell layer was firmly bonded to the polystyrene core and the wrinkled shell layer had stable properties.

[0078] After testing, the specific surface area of ​​the core-shell structure material with surface wrinkles is 10.32 mm -1 .

[0079] Example 2 of a core-shell structure material with wrinkled surface

[0080] The core-shell structure material with a wrinkled surface is composed of a three-dimensional graphene wrinkled shell layer covering a polystyrene core; the mass ratio of the three-dimensional graphene wrinkled shell layer to the polystyrene core is 1:6.1; the average particle size of the core-shell structure material with a wrinkled surface is 2 mm; the average thickness of the three-dimensional graphene wrinkled shell layer is 149.58 μm; the specific surface area of ​​the core-shell structure material with a wrinkled surface is 9.13 mm -1 The three-dimensional graphene wrinkle shell has a secondary wrinkle morphology, wherein the primary wrinkles are irregular and the secondary wrinkles are folded wrinkles.

[0081] Example 2 of a method for preparing a core-shell structure material with a wrinkled surface

[0082] (1) Soaking dried polystyrene beads (with a diameter of 4 mm) in the graphene aqueous solution (with a mass concentration of 2%) obtained in Reference Example 2 at room temperature for 2 min to allow the surface of the polystyrene beads to fully absorb the carbon source, thereby obtaining polystyrene beads absorbing the carbon source;

[0083] (2) The carbon source absorbing polystyrene beads obtained in step (1) are allowed to stand and dry at room temperature, and then placed in an oven and heated and shrunk at 120° C. for 35 minutes until they reach a stable state, thereby obtaining a core-shell structure material with a wrinkled surface.

[0084] By calculating the mass difference before and after the corrugated shell layer covers the polystyrene core, it is calculated that in the embodiment of the present invention, the mass ratio of the three-dimensional graphene corrugated shell layer to the polystyrene core is 1:6.1.

[0085] like Figure 2As shown in (a) and (b), the core-shell structure material with surface wrinkles in the embodiment of the present invention is composed of a three-dimensional graphene wrinkle shell layer covering a polystyrene core, and the average particle size is 2 mm; the three-dimensional graphene wrinkle shell layer has a secondary wrinkle morphology, wherein the primary wrinkles are irregular and the secondary wrinkles are folded wrinkles.

[0086] like Figure 2 As shown in (c), the cross-section of the core-shell structure material particles with wrinkled surfaces in the embodiment of the present invention was observed by scanning electron microscopy. The average thickness of the three-dimensional graphene wrinkled shell layer was 149.58 μm, and there was no shedding of the shell layer, indicating that the three-dimensional carbon wrinkled shell layer was firmly bonded to the polystyrene core and the wrinkled shell layer had stable properties.

[0087] After testing, the specific surface area of ​​the core-shell structure material with surface wrinkles is 9.13 mm -1 .

[0088] Example 3 of a core-shell structure material with wrinkled surface

[0089] The core-shell structure material with a wrinkled surface is composed of a polystyrene core coated with a three-dimensional multi-walled carbon nanotube and a graphene wrinkled shell layer; the mass ratio of the three-dimensional multi-walled carbon nanotube and the graphene wrinkled shell layer to the polystyrene core is 1:4.8; the average particle size of the core-shell structure material with a wrinkled surface is 2 mm; the average thickness of the three-dimensional multi-walled carbon nanotube and the graphene wrinkled shell layer is 150.43 μm; the specific surface area of ​​the core-shell structure material with a wrinkled surface is 9.12 mm -1 The three-dimensional multi-walled carbon nanotubes and graphene wrinkled shells have a secondary wrinkle morphology, wherein the primary wrinkles are irregular and the secondary wrinkles are folded wrinkles.

[0090] Example 3 of a method for preparing a core-shell structure material with a wrinkled surface

[0091] (1) Dry polystyrene beads (with a diameter of 4 mm) were immersed in the mixed aqueous solution of multi-walled carbon nanotubes and graphene obtained in Reference Example 3 (the mass concentration of multi-walled carbon nanotubes was 0.1%, the mass concentration of graphene was 2.5%, and the mass ratio of multi-walled carbon nanotubes to graphene was 1:25) at room temperature for 1.5 min to allow the surface of the polystyrene beads to fully absorb the carbon source, thereby obtaining polystyrene beads absorbing the carbon source;

[0092] (2) The carbon source absorbing polystyrene beads obtained in step (1) are allowed to stand and dry at room temperature, and then placed in an oven and heated and shrunk at 140° C. for 25 minutes until they reach a stable state, thereby obtaining a core-shell structure material with a wrinkled surface.

[0093] By calculating the mass difference before and after the corrugated shell layer covers the polystyrene core, it is calculated that in the embodiment of the present invention, the mass ratio of the three-dimensional multi-walled carbon nanotubes and graphene corrugated shell layer to the polystyrene core is 1:4.8.

[0094] like Figure 3 As shown in (a) and (b), the core-shell structure material with surface wrinkles in the embodiment of the present invention is composed of a polystyrene core coated with a three-dimensional multi-walled carbon nanotube and a graphene wrinkled shell layer, and the average particle size is 2 mm; the three-dimensional multi-walled carbon nanotube and the graphene wrinkled shell layer have a secondary wrinkle morphology, wherein the primary wrinkles are irregular and the secondary wrinkles are folded wrinkles.

[0095] like Figure 3 As shown in (c), the cross-section of the core-shell structure material particles with wrinkled surfaces in the embodiment of the present invention was observed by scanning electron microscopy. The average thickness of the three-dimensional multi-walled carbon nanotube and graphene wrinkled shell layer was 150.43 μm, and there was no shedding of the shell layer, indicating that the three-dimensional carbon wrinkled shell layer was firmly bonded to the polystyrene core and the wrinkled shell layer had stable properties.

[0096] After testing, the specific surface area of ​​the core-shell structure material with surface wrinkles is 9.12 mm -1 .

[0097] Comparative Example 1

[0098] (1) Soaking dried polystyrene beads (1 mm in diameter) in the multi-walled carbon nanotube aqueous solution (mass concentration 0.5%) obtained in Reference Example 1 at room temperature for 1 min to allow the surface of the dried polystyrene beads to fully absorb the carbon source, thereby obtaining polystyrene beads absorbing the carbon source;

[0099] (2) The carbon source-absorbing polystyrene beads obtained in step (1) are dried at room temperature, and then placed in an oven and heated and shrunk at 150° C. for 15 minutes until they reach a stable state, thereby obtaining a core-shell structure material with a wrinkled surface.

[0100] By calculating the mass difference before and after the corrugated shell layer covers the polystyrene core, it is calculated that in the comparative example of the present invention, the mass ratio of the three-dimensional multi-walled carbon nanotube corrugated shell layer to the polystyrene core is 1:11.6.

[0101] After testing, the core-shell structure material with surface wrinkles in the comparative example of the present invention is composed of a polystyrene core coated with a three-dimensional multi-walled carbon nanotube wrinkled shell layer, with an average particle size of 0.5 mm; the three-dimensional multi-walled carbon nanotube wrinkled shell layer has a secondary wrinkle morphology, wherein the primary wrinkles are irregular and the secondary wrinkles are folded wrinkles.

[0102] According to detection, the average thickness of the three-dimensional multi-walled carbon nanotube wrinkled shell is 34.43 μm.

[0103] After testing, the specific surface area of ​​the core-shell structure material with surface wrinkles is 52.83 mm -1 .

[0104] Comparative Example 2

[0105] (1) Soaking dried polystyrene beads (with a diameter of 5 mm) in the aqueous solution of multi-walled carbon nanotubes (with a mass concentration of 10%) obtained in Reference Example 1 at room temperature for 1 min to allow the surface of the dried polystyrene beads to fully absorb the carbon source, thereby obtaining polystyrene beads absorbing the carbon source;

[0106] (2) The carbon source-absorbing polystyrene beads obtained in step (1) are dried at room temperature, and then placed in an oven and heated and shrunk at 180° C. for 45 minutes until they reach a stable state, thereby obtaining a core-shell structure material with a wrinkled surface.

[0107] By calculating the mass difference before and after the corrugated shell layer covers the polystyrene core, it is calculated that in the comparative example of the present invention, the mass ratio of the three-dimensional multi-walled carbon nanotube corrugated shell layer to the polystyrene core is 1:2.

[0108] After testing, the core-shell structure material with wrinkled surface in the comparative example of the present invention is composed of a three-dimensional multi-walled carbon nanotube wrinkled shell layer covering a polystyrene core, and the average particle size is 2.5 mm; the three-dimensional multi-walled carbon nanotube wrinkled shell layer has a primary wrinkle morphology, and the primary wrinkles are folded wrinkles.

[0109] According to detection, the average thickness of the three-dimensional multi-walled carbon nanotube wrinkled shell is 318.36 μm.

[0110] After testing, the specific surface area of ​​the core-shell structure material with surface wrinkles is 2.97 mm -1 .

[0111] Application Examples 1 to 3 of a Core-Shell Structure Material with Corrugated Surface

[0112] The surface wrinkled core-shell structure material embodiments 1 to 3 are respectively applied to the field of electromagnetic wave absorption.

[0113] The core-shell structure material embodiments 1 to 3 with wrinkled surfaces were respectively encapsulated with paraffin, and the electromagnetic parameters of the samples in the 2 to 18 GHz frequency band were tested by a vector network analyzer. The reflection loss was calculated and the electromagnetic wave absorption performance was evaluated when the matching thicknesses were 0.5 mm, 1.0 mm, 1.5 mm, 2.0 mm, 2.5 mm, 3.0 mm, 3.5 mm, 4.0 mm, 4.5 mm, and 5.0 mm, respectively.

[0114] like Figure 4As shown, in the 2-18 GHz frequency band, the core-shell structure material embodiment 1 with a wrinkled surface can achieve a minimum reflection loss value of -39.63 dB when the matching thickness is 3.0 mm; when the matching thickness is 3.5 mm, the effective absorption bandwidth with a reflection loss lower than -10 dB reaches 8.8 GHz. Compared with traditional dielectric loss nanocomposites, it can produce a wider absorption peak, which can basically cover the X band and Ku band, and can be used in defense and military industries and other fields.

[0115] like Figure 5 As shown, in the 2-18 GHz frequency band, the core-shell structure material embodiment 2 with a wrinkled surface can achieve a minimum reflection loss value of -16.22 dB when the matching thickness is 5.0 mm; when the matching thickness is 3.5 mm, the effective absorption bandwidth with a reflection loss lower than -10 dB reaches 4.88 GHz.

[0116] like Figure 6 As shown, in the 2-18 GHz frequency band, when the matching thickness is 3.0 mm, the reflection loss value of Example 3 of the core-shell structure material with a wrinkled surface can reach a minimum of -28.45 dB; when the matching thickness is 3.5 mm, the effective absorption bandwidth with a reflection loss lower than -10 dB reaches 6.8 GHz.

[0117] In summary, Examples 1 to 3 of the core-shell structure material with wrinkled surfaces of the present invention have potential application prospects in the field of electromagnetic wave absorption.

[0118] Application Comparative Example 1 of a core-shell structure material with wrinkled surface

[0119] The surface wrinkled core-shell structure material comparative example 1 is respectively applied to the field of electromagnetic wave absorption.

[0120] The surface wrinkled core-shell structure material comparative example 1 was packaged with paraffin wax, and the rest was the same as application examples 1 to 3 of the surface wrinkled core-shell structure material.

[0121] After testing, the surface wrinkled core-shell structure material comparative example 1 can only reach a minimum reflection loss value of -12.6dB in the 2-18GHz frequency band when the matching thickness is 3.5mm; when the matching thickness is 4.0mm, the effective absorption bandwidth with reflection loss lower than -10dB is only 2.96GHz. Since the diameter of the polystyrene beads used in comparative example 1 is too small, the specific surface area is too large after heating and shrinking, making it difficult for the carbon source solution with a low mass concentration to form a surface wrinkled coating of suitable thickness, resulting in poor wave absorption performance of the surface wrinkled core-shell structure material obtained in comparative example 1.

[0122] Application Comparative Example 2 of a core-shell structure material with wrinkled surface

[0123] The surface wrinkled core-shell structure material comparative example 2 is respectively applied to the field of electromagnetic wave absorption.

[0124] The surface wrinkled core-shell structure material comparative example 2 was packaged with paraffin wax, and the rest was the same as application examples 1 to 3 of the surface wrinkled core-shell structure material.

[0125] After testing, the surface wrinkled core-shell structure material of Example 2 can only reach a minimum reflection loss value of -15.1dB in the 2-18GHz frequency band when the matching thickness is 2.5mm; when the matching thickness is 3.0mm, the effective absorption bandwidth with reflection loss lower than -10dB is only 4.24GHz. Since the mass concentration of the carbon source solution used in Example 2 is too high, the thickness of the coating is too large, and wrinkles are difficult to form, resulting in poor absorption performance of the surface wrinkled core-shell structure material obtained in Example 2.

[0126] Application Example 1 of a core-shell structure composite material with densely packed surface wrinkles

[0127] The core-shell structure composite material with densely packed surface wrinkles obtained by compounding the core-shell structure material with the best surface wrinkles in Example 1 of the wave absorbing performance in a periodic structure in a frame is applied to the field of electromagnetic wave absorption.

[0128] The preparation method of the core-shell structure composite material with densely packed surface wrinkles comprises the following steps:

[0129] (1) The core-shell structure material 1 with a wrinkled surface is placed in a polylactic acid rectangular groove mold 2 (with an inner length of 3 cm, an inner width of 3 cm, and a groove depth of 2 mm) coated with double-sided adhesive. Figure 7 As shown in the figure, the array is closely arranged (the number is 15 columns * 15 rows), and a single-layer adhesive composite material is obtained;

[0130] (2) 36 groups of two pieces of single-layer adhesive composite materials, each with one side not coated with double-sided tape, are connected in pairs to a polylactic acid frame structure 3 (the cavities 3-1 in the polylactic acid frame structure 3 are arranged in an array, the number is 6 columns * 6 rows, the distance between adjacent cavities 3-1 in the polylactic acid frame structure 3 is 2 mm, and the inner length of the cavity 3-1 in the polylactic acid frame structure 3 is 3 cm, the inner width is 3 cm, and the thickness of the polylactic acid frame structure 3 = 2*2 mm = 4 mm, such as Figure 8 Stacked as shown in the figure, a core-shell structure composite material with densely packed surface wrinkles is obtained.

[0131] like Fig.10 As shown, in the frequency band of 2 to 18 GHz, the effective absorption bandwidth of the composite material with a core-shell structure having a close-packed surface wrinkles in Example 1 of the present invention with a reflection loss lower than -10 dB reaches 9.26 GHz, indicating that the composite material with a core-shell structure having a close-packed surface wrinkles in Example 1 of the present invention has potential application prospects in the field of electromagnetic wave absorption.

[0132] Application Example 2 of a core-shell structure composite material with densely packed surface wrinkles

[0133] The core-shell structure composite material with densely packed surface wrinkles obtained by compounding the core-shell structure material with the best surface wrinkles in Example 1 of the wave absorbing performance in a periodic structure in a frame is applied to the field of electromagnetic wave absorption.

[0134] (1) The core-shell structure material 1 with a wrinkled surface is placed in different types of polylactic acid rectangular groove molds 2 (type 1: inner length 3 cm, inner width 3 cm, groove depth 2 mm; type 2: inner length 2.8 cm, inner width 2.8 cm, groove depth 2 mm; type 3: inner length 2.6 cm, inner width 2.6 cm, groove depth 2 mm; type 4: inner length 2.4 cm, inner width 2.4 cm, groove depth 2 mm, as shown in FIG. Figure 7 After the materials are arranged in an array (the number is: 15 rows * 15 rows, 14 rows * 14 rows, 13 rows * 13 rows, 12 rows * 12 rows), the organic silicone rubber Ecoflex-0030 is applied in the gaps between the materials respectively, and after standing and curing for 3 hours at room temperature, a single-layer cured composite material is obtained;

[0135] (2) 36 groups of 4 single-layer cured composite materials are respectively placed on a polylactic acid frame structure 3 (the cavities 3-1 in the polylactic acid frame structure 3 are arranged in an array, the number of which is 6 columns*6 rows, the distance between adjacent cavities 3-1 on the lower side of the polylactic acid frame structure 3 is 2 mm, the distance between adjacent cavities 3-1 on the upper side of the polylactic acid frame structure 3 is 2 mm+(4-1)*2 mm=8 mm, and the inner cross-section of the cavity 3-1 of the polylactic acid frame structure 3 is stepped, matching the size of each layer of composite material, and the thickness of the polylactic acid frame structure 3 is 4*2 mm=8 mm, as shown in FIG. Figure 8 , 9 As shown in the figure, 4 single-layer cured composite materials are stacked in the form of a center-aligned pyramid, and the sizes from bottom to top are: 3*3cm, 2.8*2.8cm, 2.6*2.6cm, 2.4*2.4cm, to obtain a core-shell structure composite material with densely packed surface wrinkles.

[0136] like Fig.11 As shown, in the frequency band of 2 to 18 GHz, the effective absorption bandwidth of Example 2 of the core-shell structure composite material with densely packed surface wrinkles of the present invention with a reflection loss lower than -10 dB reaches 10.048 GHz, indicating that Example 2 of the core-shell structure composite material with densely packed surface wrinkles of the present invention has potential application prospects in the field of electromagnetic wave absorption.

Claims

1. A core-shell structure material with a wrinkled surface, characterized in that: The core-shell structure material with a wrinkled surface is formed by a three-dimensional carbon wrinkled shell layer covering a foamed ball core; the mass ratio of the three-dimensional carbon wrinkled shell layer to the foamed ball core is 1:3-10; the average particle size of the core-shell structure material with a wrinkled surface is 1-3 mm; the average thickness of the three-dimensional carbon wrinkled shell layer is 70-160 μm; the specific surface area of ​​the core-shell structure material with a wrinkled surface is 6-40 mm -1 ; The three-dimensional carbon wrinkle shell has a secondary wrinkle morphology; in the secondary wrinkle morphology, the wrinkle morphology of each level is grooved wrinkles, folded wrinkles, grooved / folded wrinkles, rough protrusions or irregularities.

2. The core-shell structure material with a wrinkled surface according to claim 1, characterized in that: The carbon source of the three-dimensional carbon wrinkled shell is carbon nanotubes and / or graphene; the carbon nanotubes are multi-walled carbon nanotubes with an average length of 20 to 50 μm and an average diameter of 8 to 15 nm; the graphene sheet particle size is 4 to 8 μm; the foamed beads are one or more of polystyrene, polypropylene or polyurethane.

3. A method for preparing a core-shell structure material with a wrinkled surface as claimed in claim 1 or 2, characterized in that: The following steps are involved: (1) Soaking the dried foaming beads in a carbon source aqueous solution so that the surface of the beads fully absorbs the carbon source, thereby obtaining foaming beads that absorb the carbon source; (2) The carbon source absorbing foamed beads obtained in step (1) are allowed to stand and dry, and then heated to shrink to a stable state, thereby obtaining a core-shell structure material with a wrinkled surface.

4. The method for preparing the core-shell structure material with a wrinkled surface according to claim 3, characterized in that: In step (1), the density of the foamed beads is 1 to 2 g / cm 3 The immersion temperature is room temperature and the immersion time is 1 to 2 minutes; the particle size of the foaming balls is 4 to 5 mm; the mass concentration of the carbon source aqueous solution is 0.2 to 3.0%.

5. The method for preparing the core-shell structure material with a wrinkled surface according to claim 3 or 4, characterized in that: In step (1), the carbon source aqueous solution is prepared by adding an aqueous slurry of the carbon source into water and performing ultrasonic dispersion, or directly performing ultrasonic dispersion on the aqueous slurry of the carbon source; the ultrasonic dispersion has a frequency of 40 to 80 kHz, a power of 60 to 100 W, and a time of 2 to 4 hours.

6. The method for preparing the core-shell structure material with a wrinkled surface according to claim 3 or 4, characterized in that: In step (2), the temperature of the static drying is room temperature; the temperature of the heating shrinkage is 110 to 150° C., and the time is 15 to 60 minutes.

7. The method for preparing the core-shell structure material with a wrinkled surface according to claim 5, characterized in that: In step (2), the temperature of the static drying is room temperature; the temperature of the heating shrinkage is 110 to 150° C., and the time is 15 to 60 minutes.

8. An application of the core-shell structure material with a wrinkled surface as claimed in claim 1 or 2, characterized in that: The core-shell structure material with surface wrinkles as described in claim 1 or 2, or the core-shell structure composite material with densely packed surface wrinkles obtained by compounding in a frame with a periodic structure, is applied to the fields of electromagnetic wave absorption, catalysis, adsorption and sensing.

9. The use of the core-shell structure material with a wrinkled surface according to claim 8, characterized in that: The preparation method of the core-shell structure composite material with densely packed surface wrinkles comprises the following steps: (1) The core-shell structure material with a wrinkled surface as claimed in claim 1 or 2 is densely arranged in a rectangular groove mold coated with an adhesive to obtain a single-layer adhesive composite material; or the core-shell structure material with a wrinkled surface as claimed in claim 1 or 2 is densely arranged in a rectangular groove mold, and then an elastomer is dotted in the gaps between the materials, and after standing and curing, a single-layer cured composite material is obtained; (2) Multiple groups of single-layer adhesive composite materials are stacked in pairs in a frame structure with their uncoated surfaces connected to each other, or multiple groups of single-layer cured composite materials are stacked in a frame structure to obtain a core-shell structure composite material with densely packed surface wrinkles.

10. The use of the core-shell structure material with a wrinkled surface according to claim 9, characterized in that: In step (1), the inner length of the rectangular groove mold is ≥2 cm, the inner width is ≥2 cm, and the groove depth is 1 to 3 mm; the material of the rectangular groove mold is one or more of polylactic acid, photosensitive resin or ABS plastic; the adhesive includes one or more of double-sided tape, silicone special glue or epoxy resin strong AB glue; the elastomer includes one or more of silicone rubber, epoxy resin or polydimethylsiloxane; the temperature of the static curing is room temperature, and the time is 2 to 4 hours.

11. Use of the core-shell structure material with a wrinkled surface according to claim 9 or 10, characterized in that: In step (2), the material of the frame structure is one or more of polylactic acid, photosensitive resin or ABS plastic; the cavities in the frame structure for placing the core-shell structure composite material with dense surface wrinkles are arranged in an array; the length and width of the single-layer adhesive composite material connected to each other are equal or the length and width of the upper layer are reduced by 1 to 3 mm compared with the length and width of the lower layer; the length and width of multiple stacked single-layer cured composite materials are equal or the length and width of the upper layer are gradually reduced by 1 to 3 mm compared with the length and width of the lower layer. mm; when the sizes of the stacked single-layer adhesive composite materials or single-layer cured composite materials are equal, the frame structure spacing between adjacent cavities is 2 to 6 mm, and the inner size of the frame structure cavity matches the size of the composite material; when the sizes of the stacked single-layer adhesive composite materials or single-layer cured composite materials are unequal, the frame structure spacing between adjacent cavities on the lower side of the frame structure is 2 to 6 mm, the frame structure spacing between adjacent cavities on the upper side of the frame structure = the frame structure spacing between adjacent cavities on the lower side of the frame structure + (number of layers - 1) * gradually reduced size, and the inner cross-section of the frame structure cavity is stepped, matching the size of each layer of composite material; the thickness of the frame structure = the number of layers * the thickness of the single-layer adhesive composite material or the single-layer cured composite material.